MODERN METHODS OF COMPREHENSIVE ASSESSMENT OF THE FACTORS FOR THE FORMATION OF ALLERGIC RHINITIS IN CHILDREN WITH BRONCHIAL ASTHMA (World Bulletin of Public Health, 2024)
Nowadays, there is a tendency to increase the number of all allergic diseases, including the high prevalence of bronchial asthma (BA), as well as an increase in the number of patients with combined pathology. Allergic rhinitis is the leader in the frequency of occurrence with bronchial asthma. In the last decade, the term comorbidity has often been used as a definition of the relationship, as well as the interaction of 2 or more syndromes, diseases in one patient.